Pengembangan Lembar Kegiatan Peserta Didik Berbasis Project Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Dan Keterampilan Sosial Bagi Siswa Kelas IV Sekolah Dasar - Dyah Wulandari; Mustaji; Rr. Nanik Setyowati (LP. Ma'arif Janggan Magetan, 2022)
This study aims to: (1) produce LKPD-based Project Based Learning that is feasible to improve critical thinking and social skills for grade IV elementary school students (2) produce LKPD-based Project Based Learning that is effective for improving critical thinking for grade IV elementary school students (3) produce LKPD based on Project Based Learning which is effective to improve social skills for fourth grade elementary school students. (4) produce practical Project Based Learning-based worksheets to improve critical thinking and social skills for fourth grade elementary school students. This learning media development research refers to the ADDIE model. The research subjects were fourth grade students of SD Negeri Mojo with a total of 16 students. The research design used one group pretest-posttest. The results showed: (1) that the learning device in the form of a syllabus obtained a validation result of 86.6% and RPP obtained a validation result of 94%. The results of the validation of the pre-posttest instrument were 91.6%. While the results of LKPD validation from media experts are 90%. Based on the calculation of the Likert scale, the validation results enter the very feasible criteria. So it can be concluded that Project Based Learning LKPD to Improve Critical Thinking and Social Skills for Grade IV Elementary School Students is very feasible to use. (2) There is a moderate increase in the acquisition of pretest and posttest scores, classically completeness is only 12.5% ​​with an average pretest of 52.81. The results of the posttest classical completeness score reached 87.5% with an average posttest score of 80.94. Based on the calculation of the N-Gain score, there is an increase of 0.60 and is included in the moderate improvement criteria. (3) Observation of students' communication skills obtained results of 86.6%, participating 91.8%, and sharing 94.4%. Classically obtained an average of 92.18, with very active criteria. (4) The results of the teacher's assessment of the Project Based Learning-Based LKPD to Improve Critical Thinking and Social Skills for Fourth Grade Students scored 92.18% and the average student response questionnaire was 96.5%. From these results, according to the Likert scale calculation which is converted into a percentage, it is included in the very good criteria, which means it is very practical. Thus, it can be concluded that the LKPD Based on Project Based Learning to Improve Critical Thinking and Social Skills for Class IV Students is very practical to be used as a learning medium.